It Takes Time to Unravel the Ecology of War in Gaza, Palestine: Long-Term Changes in Maternal, Newborn and Toddlers’ Heavy Metal Loads, and Infant and Toddler Developmental Milestones in the Aftermath of the 2014 Military Attacks - Nabil al Baraquoni (International Journal of Environmental Research and Public Health, 2020)
Toxicant, teratogen and carcinogen metal war remnants negatively affect human health. The current study analyzes, first, the persistence of heavy metal contamination in newborn hair in four cohorts across time in Gaza Palestine; second, the change in mothers’ and infants’ heavy metal contamination from birth to toddlerhood; and third, the impact of heavy metal contamination on infants’ and toddlers’ growth and development. The hair of newborns was analyzed for twelve heavy metals by Inductively Coupled Plasma Mass Spectrometry (ICP/MS) in cohorts recruited at delivery in 2011, 2015, 2016, and 2018–2019. In the 2015 cohort, mothers’ hair samples were taken at delivery, and toddlers and mothers hair were also analyzed 18 months later. Growth levels of infants at six months and toddlers at 18 months were assessed according to World Health Organization (WHO) standards according to a mother report and pediatric check-up, respectively. 1. The level of metal contamination in utero was persistently high across 8 years, 2011, 2015, 2016, 2019, following three major military attacks (2009, 2012, 2014). 2. The 2015 cohort babies exposed in utero to attacks in 2014 at six months showed association of high load at birth in mother of arsenic and in newborn of barium with underweight, of barium and molybdenum in newborn with stunting. 3. Eighteen months after birth, toddlers had a higher level of metals in hairs than when they were born, while, in their mothers, such levels were similar to those at delivery, confirming persistence in the environment of war remnants. Underweight and stunting, both in infants and toddlers, were higher than reported for previous years, as well as being progressive within the cohort. Severe environmental factors, metal contamination and food insecurity put Gaza’s infant health at risk.